Evaluation method of fracability of shale oil reservoir considering influence of interlayer - LIU Yexuan,LIU Xiangjun,DING Yi,ZHOU Xin,LIANG Lixi (Youqicang pingjia yu kaifa)
The physical properties of shale oil reservoir are extremely poor, so it is necessary to form a network fracture system through volume fracturing to realize economic and effective development. However, there are lower permeability interlayers both in the top and bottom of shale oil reservoirs, so to master the fracture propagation law of reservoir with interlayers is the key for the successful fracturing of shale oil. With the help of the numerical simulation software, RFPA, of the rock fracture damage analysis system, the influencing factors of fracture propagation in the reservoir interlayers are studied. On the premise of considering the heterogeneity of strata, and by the comprehensively consideration of the elastic modulus, Poisson's ratio, uniaxial compressive strength, tensile strength, horizontal stress difference and interlayer stress difference of the reservoir, the fracability of shale oil reservoir is evaluated by the analytic hierarchy process. The results show that the elastic modulus of the reservoir interlayer, the difference of horizontal in-situ stress and the uniaxial compressive strength of the reservoir are negatively correlated with the degree of crack propagation. As these parameters increase, the cracks are more difficult to expand. However, there is a positive correlation between the ratio of tension and compression of reservoir and the stress difference between layers of reservoir and the degree of fracture propagation, that is, the increase of tensile strength and interlayer stress difference will help to increase the scale of fracture propagation, and the larger interlayer stress difference will make the fractures pass through the interlayers and continue to develop in the interlayer. Meanwhile, the mathematical model of the fracability is established by the analytic hierarchy process in fuzzy mathematics, and applied to the fractured wells in the work area. The predicted results are consistent with the experimental microseismic monitoring results, and the research results can provide reference for shale oil fracturing reform.